Anti-diabetic effect of agarwood leaf extracts on straptozotocin-induced type II diabetic ICR mice - Fayyadh, Aws Ali (Tanjong Malim, 2019)
Anti-diabetic effect of agarwood leaf extracts on straptozotocin-induced type II diabetic ICR mice by Fayyadh, Aws Ali